Optimizing Trichoderma longibrachiatum Pellets with Spent Mushroom Substrate: A Study on Conidial Viability and Shelf Life - Kaewkhon, Waraporn; Naksupan, Nikhom; Kamtaeja, Somboon; Suwandee, Preedaporn; Molamsa, Sabaiprae; Inpan, Wannakarn (Journal of Food Health and Bioenvironmental Science, 2024)
Spent mushroom substrate (SMS), a byproduct of mushroom production, is commonly used as growth media in plant nurseries and horticulture. This study aimed to develop Trichoderma longibrachiatum pellets using SMS to extend conidial shelf life and enhance efficiency for biological control. T. longibrachiatum strains isolated from paddy field soils in Phayao and Chiang Rai provinces were formulated into pellets using SMS and diatomaceous earth (DE) across four formulations. Each formulation contained viable conidia of T. longibrachiatum at a concentration of 2×10⁷ conidia/mL of distilled water, with varying ratios of SMS and DE. The pellets were characterized based on weight, diameter, water solubility, and conidial shelf life after storage at 4°C for 60 days. Formulations 2–4 showed a significant increase in weight compared to Formulation 1, depending on the percentage of DE. The average pellet diameters ranged from 9.40 ± 0.27 mm (Formulation 1) to 10.89 ± 0.65 mm (Formulation 4). Water solubility tests revealed significant differences among the formulations (P < 0.05). Formulation 1 had the longest dissolution time (11.12 ± 0.89 min), while Formulation 4 had the shortest (0.26 ± 0.08 min). All formulations maintained conidial viability when cultured on Trichoderma Selective Media (TSM). Based on water solubility and conidial viability, Formulation 4 emerged as the optimal formulation for potential use in biological control applications in agriculture.